PROFESSIONAL TASKS IN THE EDUCATIONAL SYSTEM OF TRAINING MATHEMATICIANS-TEACHERS - ZharovV. K.; Esonov M. M. (Galaxy International Interdisciplinary Research Journal, 2022)
In modern mathematics education, there is a dilemma whether a graduate of the Faculty of Mathematics of a pedagogical university should know and master the methods of teaching or still firmly know the basics of a real discipline. Obviously, this question would have been an artificial question 20-30 years ago, but now a significant reduction in teaching hours in geometry programs, bringing them to a volume of three semesters leads us to disappointing conclusions. Some part of the aspect of the attitude to professional tasks this article is devoted to future specialists in the field of mathematics who are able to develop abstract thinking in students - future ones: biologists, engineers, physicists, etc.